Prognostic utility of monocyte distribution width in critically ill patients - Soo, Ki Yang; Ramly, Nur Fariza; Md Ralib, Azrina; A. Talib, Norlelawati (Kugler Publication, 2022)
Background Sepsis is one of the leading causes of intensive care unit (ICU) admission and mortal- ity in Malaysia. Delayed recognition of sepsis is associated with increased morbidity and mortality. Monocyte distribution width (MDW) represents the width of a set of monocyte volume values, which increases as infection progress in severity. Its mea- surement is one of the haematologic parameter of complete blood count, hence, it does not incur added cost and is widely available. We evaluated the prognostic ac- curacy of MDW. Methods This was a prospective cohort study of 100 patients who are grouped into sepsis and non-sepsis according to the Sepsis-3 definition. This study enrolled adults, age 18 years and above, whose evaluation included a complete blood count with differ- ential upon admission to ICU. Exclusion criteria included patient refusal to join the study, readmission to ICU within 12 hours and prior study enrolment. MDW and WBC were collected on admission to ICU and for subsequent 3 days. The study had ob- tained approval from the IIUM Research Ethics Committee (Number 2020-079). Results A total of 100 patients were recruited in the study. Twenty-three patients (23%) died within 30 days of ICU admission. MDW were predictive of 30-day mortality with a cut-off point of 25.97. Patients with on admission MDW higher than this cut-off point were more likely to die with 30 days compared to those with lower value. WBC on admission and throughout 3 days were not predictive of 30-day mortality. Conclusion MDW is an effective prognosis tool of mortality upon admission to ICU. As part of the differential in CBC, MDW makes a cost effective and widely available test at present. Early prediction of death allows for risk stratification for patients admitted to the ICU.